Exploring the impact of professional soccer substitute players on physical and technical performance - Pengyu Pan; Fangbin Li; Bo Han; Bo Yuan; Tianbiao Liu (BMC, 2023)
Abstract Background Substitutions are generally used to promote the match performance of the whole team. This study aimed to analyze the performance of substitute players and explore the performance difference among substitute players, completed players, and replaced players across each position. Methods Chinese Super Soccer League (CSL) matches in the season 2018 including 5871 individual observation from 395 professional soccer players were analyzed by establishing linear mixed models to quantify the performance difference among substitute players (SP) (n = 1,071), entire match players (EMP) (n = 3,454), and replaced players (RP) (n = 1,346), and then separately for each position (central defenders, fullbacks, central midfielders, wide midfielders, and attackers). Results The results show SP display higher high intensity distance and sprint distance significantly (p < 0.05) relative to playing time than RP and EMP. SP in offensive positions (attackers, wide midfielders) showed significantly higher (p < 0.05) passing and organizing performance such as passes, ball control, short passes, and long passes than RP or EMP. The scoring performances of central midfielders of SP including goals, shots, and shots on target are significantly higher (p < 0.05) than RP or EMP. Central defenders of SP showed higher shot blocks and pass blocks (p < 0.05) while lower passing and organizing performance (p < 0.05). Conclusion Depending on different playing positions, substitute players could indeed improve physical and technical performance related to scoring, passing, and defending as offensive substitute players can boost organizing performance and substitute defenders enhance defending performance. These could help coaches better understand substitute players' influence on match performance and optimize the substitution tactic.